Fracture Shaft of Femur in Children with Newly Designed Femoral Brace - Mahara, DP; Lamichhane, A; Acharya, P; Shrestha, GC (Journal of Institute of Medicine Nepal, 2013)
Introduction: With the initial traction and secondary hip spica conservative treatment of fracture shaft of femur in children is an established technique of management all over the world. Three-six weeks of traction followed by another 6-8weeks of immobilization in spica cast at home takes away precious school going time of the children and professional earning time of the parents in our part of the world. The situation compelled us to think and design an Orthosis that not only splints the fractured femur but also maintains the continuous traction and acceptable alignment right from the beginning and allows early mobilization thereby avoiding need of long hospital stay, immobilization on spica cast and abstinence from school. Methods: This Orthosis has been used successfully in 9 children with fractured shaft of femur, age ranged from 3 to 9 years with average age of 5 years. Initially the patients were put on skin traction. In the meantime, measurement of body parts was taken by an orthotist for fabrication of the brace, which was made available on second week. In presence of the orthotist the brace was applied and its fitting and pressure points were properly evaluated. The patients were discharged the next day and asked to follow up at 2,4,6,9 and 12 weeks with a roentgenogram at every visit. Patients were encouraged to bear weight with the affected limb with the brace on after achieving clinical union. Brace was removed after achieving radiological union. Results: One patient did not turn up for follow up after application of brace. So, out of the ten patients, nine were included in this study as they had follow up of at least 12 weeks. Seven cases were male and two female. The average age of the patients was 5 years (range 3 to 9 years). The follow up period ranged from 12 weeks to 3 years with average period of 9.3 months. Radiological union was seen to occur at 12th week in 7 patients and 9th week in 2 patients and the brace was discarded at that time. Fracture united in all patients without any obvious angular, rotational deformities and limb length discrepancy. Conclusion: Preliminary findings of this study showed the use of this Orthosis in the treatment of fracture shaft of femur in children has proved to be as good as the traditional method with distinct advantages of treating at home and early mobilization with the brace on. DOI: http://dx.doi.org/10.2126/joim.v35i1.8892 Journal of Institute of Medicine, April, 2013; 35:18-22